THE EFFECTIVENESS OF IMPLEMENTATION OF NEW ONLINE-BASED STUDENT ADMISSION SYSTEM AT STATE SENIOR HIGH SCHOOLS (SMAN) GORONTALO - Razak, Intan Abdul; Suking, Arifin; Hasan, Sutinsi (Faculty of Education Universitas Negeri Malang, 2022)
This study aims to determine (1) the online-based registration process for the new student admissions system, (2) the online-based selection process for the new student admissions system, (3) the online-based selection process for the announcement of the results of the new student admissions. The method in this study uses a quantitative approach to the type of explanatory research. The subject of this research is the committee for accepting new students based online with a total of 86 committee members. The sampling technique in this study used a purposive sampling technique. Data collection techniques using questionnaires, interviews, observations, and documentation and data analysis using descriptive analysis of presentations and criteria. The results show that: (1) the online-based new student admissions system registration process is very effective (2) the online-based new student admissions system selection process is quite effective (3) the selection process announcement is applied in the admission of participants online-based new students are on the effective criteria. This states that the application of an online-based new student admission system at SMA Negeri Se Kota Gorontalo is in the effective category so that the school must seek to cooperate and communicate with the local Education Office so that the PPDB Online process can run effectively and efficiently in every school in the province. Gorontalo City.. To be suggested: For Dikbudpora, namely Improving the quality and quantity of bandwidth from the online-based application for new student admissions. For Schools Improving the ability of committee operators in using applications. It is necessary to thoroughly socialize the community or parents of students regarding the online-based acceptance mechanism for new students.